Addressing Disparities in Urological Training Across Low- and Middle-Income Countries. Comment on Baqain et al. Post-Graduate Urology Training in Low- and Middle-Income Countries. Soc. Int. Urol. J. 2024, 5, 339–348 - Saleh Abdelkerim Nedjim; Chandra Shekhar Biyani (Société Internationale d’Urologie Journal)
The global demand for urologists is increasing, particularly in low- and middle-income countries (LMICs), where urological problems continue to pose a significant public health burden [...]